THE EFFECT OF LOCUS OF CONTROL, CULTURAL INTELLIGENCE AND ACADEMIC SELF-EFFICACY ON THE ACADEMIC ADJUSTMENT AMONG YEMENI STUDENTS IN TURKEY - Gawas, Ahmed Gamal Ahmed (American International Journal of Social Science Research, 2022)
The current study aims to examine the correlations between both of locus of control, academic self-efficacy, cultural intelligence and academic adjustment. It also seeks to predict academic adjustment from locus of control, academic self-efficacy and cultural intelligence. In addition, the present study aims to examine whether cultural intelligence mediates the relationship between academic self-efficacy and academic adjustment. In this study 262 Yemeni students studying in Turkish universities participated. A list taken from the Rotter's scale was developed to measure the locus of control. College academic self-efficacy scale (CASES), cultural intelligence scale (CIS) and the student adaptation to college questionnaire (SACQ) were used to collect data of study. The results show that there are statistically significant correlations among all the variables of study. Results also indicated that academic adjustment was be predicted from academic self-efficacy and locus of control. Furthermore, results show that the cultural intelligence did not mediate the relationship between academic self-efficacy and academic adjustment. There are statistically significant differences in academic self-efficacy and academic adjustment due to educational level. There are also differences in academic adjustment due to gender.JEL Classification Codes: H75.